Environment Friendly Salt Coating For Root Pruning Of Sweet Pepper Seedlings - Shrestha, Surendra Lal; Kang, Won-Hee (Journal of Agriculture and Environment, 2013)
This study was done to minimize excessive growth and root mat formation which is a problem during preparation of seedlings in sweet pepper (Capsicum annuum L.) seedlings. The experiment was laid out in a completely randomized design (CRD) with 3 replications. Hybrid CV. ‘Sonik’ seeds were planted in plug trays coated with latex paint containing 0%, 1%, 3%, 5%, 7%, 10% and 15% NaCl (w/v) and compared with an uncoated control. Results showed that NaCl coating significantly minimized excessive growth rate and root mat formation. Seedlings from the treatment produced more fibrous roots. Even though before transplanting, untreated seedlings were taller with longer root length, significantly higher fresh and dry weight of shoots and roots; after transplanting, seedlings from NaCl coated trays showed better performance with taller plants, longer roots, and higher fresh and dry weights of shoots and roots. The 7% NaCl treatment gave superior performance among the treated and control plants. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 74-80 DOI: http://dx.doi.org/10.3126/aej.v12i0.7566